2021
DOI: 10.1002/ps.6490
|View full text |Cite
|
Sign up to set email alerts
|

Successful development and implementation of a practical proactive resistance management plan for Bt cotton in Australia

Abstract: This article describes the design and > 20 years of effective implementation of a proactive resistance‐management plan for transgenic Bacillus thuringiensis (Bt) cotton that targets Helicoverpa armigera (Hübner) and Helicoverpa punctigera (Wallengren) in Australia, considering pest biology and ecology, insights from resistance‐evolution modelling, and the importance of the human component to effective implementation. This is placed in the context of processes associated with adaptive resource management. Bt co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
(100 reference statements)
0
11
0
Order By: Relevance
“…In Australia, where resistance management rules have been more stringent than in the United States, decreased susceptibility of H. armigera to Cry1Ac produced by Bt cotton has not been reported after 25 years 64 . A minimum refuge of 70% non‐Bt cotton was required in Australia from 1996 to 2003 for cotton producing only Cry1Ac 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, where resistance management rules have been more stringent than in the United States, decreased susceptibility of H. armigera to Cry1Ac produced by Bt cotton has not been reported after 25 years 64 . A minimum refuge of 70% non‐Bt cotton was required in Australia from 1996 to 2003 for cotton producing only Cry1Ac 65 .…”
Section: Discussionmentioning
confidence: 99%
“…62 In Australia, where resistance management rules have been more stringent than in the United States, decreased susceptibility of H. armigera to Cry1Ac produced by Bt cotton has not been reported after 25 years. 64 A minimum refuge of 70% non-Bt cotton was required in Australia from 1996 to 2003 for cotton producing only Cry1Ac. 65 In 2004, when farmers in Australia switched completely from Cry1Ac cotton to Cry1Ac + Cry2Ab cotton with a 10% non-Bt cotton refuge required, H. armigera was still fully susceptible to Cry1Ac, maximizing the immediate and longterm benefits of the two-toxin cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, annual monitoring in Arizona showed that no pink bollworm larvae were found on cotton from 2010 to 2018, and no wild pink bollworm moths were found in fields from 2013 to 2018. Based on similar conditions in other states, the US Secretary of Agriculture announced in October 2018 that pink bollworm had been eradicated in the continental commercial cotton producing areas in the United States [ 16 , 70 , 71 , 72 , 73 , 74 , 75 ]. In India, the cotton seeds provided by cotton seed companies not only include 450 g of Bt cotton seeds per bag but also contain 120 g of non-Bt cotton seeds in order to set up structural refuges.…”
Section: Resistance Management Tactic Type Ii: Seed MIX Refuge For Ol...mentioning
confidence: 99%
“…At present, the insecticidal protein species expressed by commercially cultivated Bt cotton around the world include Cry1Ac, Cry2Ab, and Vip3Aa, with an annual planting area of more than 33 million hectares [ 2 , 5 , 13 ]. This plays an important role in controlling the occurrence of lepidopteran pests (see Tabashnik and Carrière (2019) [ 14 ], Li et al, (2019) [ 15 ], Knight et al, (2021) [ 16 ] review).…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic crops producing insecticidal proteins from Bacillus thuringiensis (Bt) have improved control of some key pests and reduced conventional insecticide use, while remaining safe for most nontarget organisms (Gould et al 2016, Dively et al 2018, ISAAA, 2019, Romeis and Meissle 2020, Knight et al 2021, Krogh et al 2020, Tabashnik et al 2021). However, these benefits decrease when pests evolve practical resistance to Bt crops (Tabashnik and Carrière 2019).…”
mentioning
confidence: 99%